2015
DOI: 10.1097/ogx.0000000000000275
|View full text |Cite
|
Sign up to set email alerts
|

Letrozole, Gonadotropin, or Clomiphene for Unexplained Infertility

Abstract: BACKGROUND-The standard therapy for women with unexplained infertility is gonadotropin or clomiphene citrate. Ovarian stimulation with letrozole has been proposed to reduce multiple gestations while maintaining live birth rates. METHODS-We enrolled couples with unexplained infertility in a multicenter, randomized trial. Ovulatory women 18 to 40 years of age with at least one patent fallopian tube were randomly assigned to ovarian stimulation (up to four cycles) with gonadotropin (301 women), clomiphene (300), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
125
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(129 citation statements)
references
References 22 publications
4
125
0
Order By: Relevance
“…The current study reported a clinical pregnancy rate of 25% and a live birth rate of 21.3% for the total letrozolestimulated cycles, regardless of the ovulation triggering protocol; the rates that accord with those formerly stated in various studies evaluated letrozole superovulation in women with UI (table 4) [11][12][13][14][15][16] . However, dual triggering by FSH/hCG compared to hCG alone improved the outcome of Letrozole-stimulated IUI cycles manifested as significantly higher pregnancy rate pre-cycle (12.5% vs. 5.8%: p=0.049) and per-woman (33.33% vs. 16.67%: p=0.049), and a significantly higher live birth rate (29.6% vs, 12.5%; p= 0.039).…”
Section: Discussion:-supporting
confidence: 65%
See 2 more Smart Citations
“…The current study reported a clinical pregnancy rate of 25% and a live birth rate of 21.3% for the total letrozolestimulated cycles, regardless of the ovulation triggering protocol; the rates that accord with those formerly stated in various studies evaluated letrozole superovulation in women with UI (table 4) [11][12][13][14][15][16] . However, dual triggering by FSH/hCG compared to hCG alone improved the outcome of Letrozole-stimulated IUI cycles manifested as significantly higher pregnancy rate pre-cycle (12.5% vs. 5.8%: p=0.049) and per-woman (33.33% vs. 16.67%: p=0.049), and a significantly higher live birth rate (29.6% vs, 12.5%; p= 0.039).…”
Section: Discussion:-supporting
confidence: 65%
“…However, dual triggering by FSH/hCG compared to hCG alone improved the outcome of Letrozole-stimulated IUI cycles manifested as significantly higher pregnancy rate pre-cycle (12.5% vs. 5.8%: p=0.049) and per-woman (33.33% vs. 16.67%: p=0.049), and a significantly higher live birth rate (29.6% vs, 12.5%; p= 0.039). The reported pregnancy and live birth rates in the FSH/hCG trigger group are superior to those reported in diverse studies evaluating different letrozole-stimulated IUI protocols in women with UI (table 4) [11][12][13][14][15][16] . To our knowledge, this is the first trial planned to appraise the effect of FSH/hCG dual triggering in letrozole-stimulated cycles in ladies with UI.…”
Section: Discussion:-mentioning
confidence: 85%
See 1 more Smart Citation
“…In couples with unexplained infertility undergoing IUI, where it has been shown that OS significantly increases LBR when compared to natural cycles [4,21] , only one study comparing CC and letrozole reported LBR as an outcome [22] . The Assessment of Multiple Intrauterine Gestations from Ovarian Stimulation (AMIGOS) trial analyzed LBR as a secondary outcome and found rates with letrozole (18.7%) statistically noninferior to rates with CC (23.3%) [22] . Cumulative LBR seem to be higher with both treatments in our study, probably because the patients included had no history of infertility, and only cryopreserved donor sperm was used.…”
Section: Discussionmentioning
confidence: 99%
“…cretion, which stimulates the ovaries, resulting in increased oestrogen levels. This effect is helpful in reproductive medicine [24]. For this reason, AIs are not suitable for endocrine therapy for breast cancer treatment in pre-menopausal women.…”
mentioning
confidence: 99%